Peranan Sekretaris dalam Kelancaran Administrasi pada Kejaksaan Negeri Banda Aceh - Wulandari, Novita; Djamil HS, M (Journal of Law and Economics, 2022)
.The purpose of this study is to explain the role of the secretary in maintaining smooth administrative operations in the Banda Aceh District Attorney's Office. Efficient and effective administration is critical to ensuring that work processes at the Attorney General's Office run smoothly and comply with applicable legal requirements. A qualitative approach was used in this study, and data were collected through interviews, observations, and document research. The findings show that the secretary plays an important role in the administrative management of the Banda Aceh District Public Prosecutor's Office. This role includes drafting and managing various documents and letters, arranging meetings, managing information, and coordinating with other departments within the judiciary. The Director is also responsible for maintaining the Secretariat and ensuring the confidentiality of important documents relating to the Office of the Attorney General's duties and responsibilities. In this case, the secretary's ability to systematically assemble, store, and manage documents is critical to maintaining the security of confidential information. In addition, secretaries help ensure effective communication between the prosecution and external parties such as courts, other law enforcement agencies, and the public. Good communication skills and effective leadership are key factors that enable secretaries to perform their duties effectively. In summary, the role of the Commissioner is very important for the smooth running of the Banda Aceh District Attorney's Office. By properly managing documents, arranging meetings, managing information, and communicating effectively, the secretary can make a significant contribution to the efficiency and effectiveness of the work of the Banda Aceh District Prosecutor's Office. It is hoped that this study will lead to a better understanding of the role of secretaries in prosecution administration and provide useful recommendations for improving administrative performance in the future.